Prevalence and Associated Factors of Substance Use Male Population in East African Countries: A Multilevel Analysis of Recent Demographic and Health Surveys From 2015 to 2019 - Kenaw Derebe Fentaw; Setegn Muche Fenta; Hailegebrael Birhan Biresaw (SAGE Publishing, 2022)
Background: East Africa is still home to one of the world's highest rates of substance user. Substance use is primarily associated with male behavior and is becoming one of the region's most public health issues. Methods: The study included data from 11 East African countries' Demographic and Health Surveys. About 55 307 men were enrolled in the study and multilevel logistic regression model was applied Result: East African countries had a 43.70% prevalence of substance abuse coverage. Education level, age, current working status, marital status, wealth index, media exposure, residence, and nation were all found to be statistically associated with substance use of males. Conclusion: In East African countries, the prevalence of substance abuse among men was high. As a result, substance control programs should focus on the poor, not (least) educated, rural people, and adult age groups, who are the region's most vulnerable social groups.